Moral distress in nurses caring for patients with Covid-19 - Silverman, Henry J (Nursing ethics, 2021)
Background:Moral distress occurs when constraints prevent healthcare providers from acting in accordance with their core moral values to provide good patient care. The experience of moral distress in nurses might be magnified during the current Covid-19 pandemic.Objective:To explore causes of moral distress in nurses caring for Covid-19 patients and identify strategies to enhance their moral resiliency.Research design:A qualitative study using a qualitative content analysis of focus group discussions and in-depth interviews. We purposively sampled 31 nurses caring for Covid-19 patients in the acute care units within large academic medical systems in Maryland and New York City during April to June 2020.Ethical considerations:We obtained approval from the Institutional Review Board at the University of Maryland, Baltimore.Results:We identified themes and sub-themes representative of major causes of moral distress in nurses caring Covid-19 patients. These included (a) lack of knowledge and uncertainty regarding how to treat a new illness; (b) being overwhelmed by the depth and breadth of the Covid-19 illness; (c) fear of exposure to the virus leading to suboptimal care; (d) adopting a team model of nursing care that caused intra-professional tensions and miscommunications; (e) policies to reduce viral transmission (visitation policy and PPE policy) that prevented nurses to assume their caring role; (f) practicing within crisis standards of care; and (g) dealing with medical resource scarcity. Participants discussed their coping mechanisms and suggested future strategies.Discussion/Conclusion:Our study affirms new causes of moral distress related to the Covid-19 pandemic. Institutions need to develop a supportive ethical climate that can restore nurses’ moral resiliency. Such a climate should include non-hierarchical interdisciplinary spaces where all providers can meet together as moral peers to discuss their experiences.